2018
DOI: 10.3389/fcomm.2018.00018
|View full text |Cite
|
Sign up to set email alerts
|

Are you Concerned? Patient Testimonials in Medical Communication Affect Healthy Recipients' Emotions and Memory

Abstract: Medical communication and health care intervention programs often include testimonials (i.e., an account of individuals' experiences) when addressing health-related topics. Numerous findings provide evidence of the effectiveness of such testimonials on intentions for health behavior change. However, little is known about whether and how testimonials affect healthy lay people's reception of health information (e.g., in journalistic reports about medical innovations). The present studies tested whether using pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
5
0
2
Order By: Relevance
“…In line with the ELM [ 30 ], personal involvement and interest may contribute to systematic information processing and may reduce the impact of testimonials based on heuristics. Accordingly, earlier research indicated that the perceptions of testimonials by unconcerned people may differ from those with past or current health problems on the one hand [ 33 ]. Yet, some studies demonstrated positive effects of testimonials on hypothetical psychological treatment decisions [ 25 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the ELM [ 30 ], personal involvement and interest may contribute to systematic information processing and may reduce the impact of testimonials based on heuristics. Accordingly, earlier research indicated that the perceptions of testimonials by unconcerned people may differ from those with past or current health problems on the one hand [ 33 ]. Yet, some studies demonstrated positive effects of testimonials on hypothetical psychological treatment decisions [ 25 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, most research on the effects of health-related testimonials has focused on patient narratives in decision aids and hypothetical medical treatment or screening choices by patients [32]. Much less is known about how unconcerned people process health testimonials with respect to preventative purposes [33]. More remarkably, very few studies have investigated the effects of testimonials on views about psychological interventions such as eMHSs, and the existing research yielded indecisive findings [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…This seems particularly promising as attempts to influence conspiracy believers are often unsuccessful, especially when the communication comes from authorities (Imhoff et al, 2018;. In the current case, personalised health communication might be more successful (Sassenrath, Greving, & Sassenberg, 2018;Sassenrath, Sassenberg, & Greving, 2017). When talking, for instance, about the COVID-19 vaccination, it could be a first step to reveal one's own positive vaccination intentions to close others who endorse conspiracy beliefs.…”
Section: Practical Implicationsmentioning
confidence: 94%
“…In der vorliegenden Studie wurden nur positive Aussagen über eMHSs verwendet, was bei Nutzerbewertungen unrealistisch erscheinen mag. Infolgedessen sollte zukünftige Forschung die Valenz von Testimonials variieren [ 25 ].…”
Section: Diskussionunclassified